Analisis Faktor-Faktor Green Purchase Intention untuk Meningkatkan Potensi Lokal Usaha Tanaman Organik dan Ketahanan Pangan di Kota Bandung - Aryanti Ratnawati; Louisisani Mansoni (Jurnal Sekretaris dan Administrasi Bisnis, 2018)
The intention of purchasing green products is the desire or expression of one's intention to commit to activities that support environmental friendliness, green purchase intention is influenced by several factors such Ecological Knowledge and Ecological Affect is everything related with the expression of emotions on the environment with a correlation of 3 factors: attention to self, concern for others, and attention to the environment. The research method used in this research is the Survey method, while the type of research uses Causal Asosiative research with the indicator of the research level of consumer knowledge to the environment, the level of consumer affection to the environment, consumer interest towards the purchase of organic plants and the increase of local potential for organic plants in Bandung.The method of analysis used is multiple linear regression analysis is known to obtain the value Fcount 38.4196> F_tables 3.03 it can be interpreted that simultaneously factor-fator Ecological (Knowledge and Affect) have a significant influence on Green Purchase Intention. Based on the identification of Ecological factors and its effect on Green Purchase Intention, it can be seen that the influence of local potential increase in Bandung is t_count value 11, 160> t_table 1,683 because t_hitung> t_tabel it can be explained that Green Purchase Intention has an effect on increasing the Local Potential of Organic Plants in the city of Bandung. Green purchase intention (X1) and local potential (X2) on food security in Bandung can be shown from the calculation coefficient of determination as follows by 0.46 That is, green purchase intention (X1) and local potential (X2) 46 % in increasing food security of green vegetable production (Y). while the remaining 54.0% is influenced by other factors that are not included into the research model. Keywords: Ecological Knowledge, Ecological Affect, Green Purchase Intention, Local Potential